(untitled) (Tesis Psicológica, 2020)
Background:The main objective of this study is to describe the perspective of human life cycle in childhood, considering the variables cognition, emotion and behavior in the city of Armenia-Quindío, Colombia. Objective:It was proposed from the psychological discipline and from the particular interest of characterizing different age groups in the Colombian context, specifically in the Quindío region. Methodology: A quantitative methodological approach is proposed, given that it corresponds with the descriptive, analytical logic and with the intention of generalize the results. With a descriptive-transversal design, the battery SENA (Sistema de Evaluación para Niños y Adolescentes) was applied, oriented to collect information from multiple sources, in this opportunity was possible to work with a n = 75. The results were discriminated by type of source that provided the information, considering that young children do not respond to the self-report questionnaire, because it requires literacy skills that due to biological and school development conditions haven’t been achieved. A total of 75 questionnaires were applied from the family perspective, 47 from the self-report perspective and 28 from the school. Results:The results show that according to the self-report presented by the participants, 4 out of 5 children are involved in a situation of contextual risk for ages between 7 to 11 years old; from the family perspective, is considered that 1 out of 2 participants present risks like possible school bullying, risk of self-harm and risk of aggression or harm to others. In addition, possible effects on the development of executive functions and the presence of behavioral and emotional problems, possibly related to imbalances and mismatching from the context. Conclusion: Finally, it is considered fundamental to adopt a new form of approaching to the study of development and life cycle, which includes conditions closer to the population group of interest, taking into account individualdi fferences, the continuous and discontinuous form of development and conditions of the region where they belong.